2017
DOI: 10.1302/0301-620x.99b11.bjj-2016-0655.r2
|View full text |Cite
|
Sign up to set email alerts
|

The unsuspected prosthetic joint infection

Abstract: Following revision of TKA and THA for aseptic diagnoses, around 10% of cases were found to have positive cultures. In the knee, such cases had inferior infection-free survival at two years compared with those with negative cultures; there was no difference between the groups following THA. Cite this article: Bone Joint J 2017;99-B:1482-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 21 publications
4
45
0
1
Order By: Relevance
“…However, this is consistent with the absence of clinical radiographic findings associated with S. epidermidis implant-associated bone infections, 35 and aseptic loosening of total joint replacements. 12,13 These observations are also consistent with the findings of Lankinen et al, who demonstrated similar bone destruction tendencies to our results with a rabbit model. 36 On SEM analysis, RP62A produced less biofilm compared with USA300.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…However, this is consistent with the absence of clinical radiographic findings associated with S. epidermidis implant-associated bone infections, 35 and aseptic loosening of total joint replacements. 12,13 These observations are also consistent with the findings of Lankinen et al, who demonstrated similar bone destruction tendencies to our results with a rabbit model. 36 On SEM analysis, RP62A produced less biofilm compared with USA300.…”
supporting
confidence: 94%
“…However, S. epidermidis is also considered to be an opportunistic pathogen, as it causes infections in immunocompromised patients with implants . S. epidermidis is also present on prosthetic joint infection (PJI), and implants removed for aseptic prosthesis loosening . Interestingly, late‐start chronic (low‐grade) PJI, which are challenging to diagnose from unspecific clinical signs, false‐negative cultures, and low values of serum biomarkers, often contain CNS as the hidden pathogen .…”
mentioning
confidence: 99%
“…This picture can be seen when positive intraoperative cultures are obtained in revision surgeries due to clinical suspicion of aseptic causes, especially if performed < 5 years after the index procedure, and if mechanical or functional causes could not be identified by conventional investigations. 15…”
Section: Clinical Diagnosis Of Periprosthetic Joint Infection (Signs mentioning
confidence: 99%
“…É o que pode acontecer na circunstância de culturas positivas intraoperatórias em cirurgias de revisão com suspeita clínica de causas presumivelmente assépticas, sobretudo quando realizadas em cirurgias com um seguimento < 5 anos após a cirurgia de base, e nas quais causas mecânicas ou funcionais não podem ser identificadas por investigações convencionais. 15…”
Section: Diagnóstico Clínico Da Infecção Articular Periprotética (Sinunclassified
“…The widespread gram-negative agents are Pseudomonas aeruginosa , Acinetobacter baumanii , Klebsiella pneumoniae , Proteus spp., Enterobacter spp., Escherichia coli [2], [3], [4]. Despite recent technological advances in cultural methods, an overwhelming 10% to 42% microbial causes of all periprosthetic infections remain unidentified [5], [6].…”
Section: Introductionmentioning
confidence: 99%